Brand Image dan Minat Pembelian Kembali di Harlan+Holden Pacific Place Jakarta (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The food and beverage service industry has undergone significant development in major urban centers such as DKI Jakarta, leading to heightened competition among competitors. As one of the new cafes, Harlan + Holden must possess the capability to thrive amidst this intense competition. However, the lack of research specifically addressing Harlan + Holden poses challenges in assessing its competitive ability against its counterparts. The objective of this study was to evaluate Harlan + Holden's capacity to cultivate brand image and stimulate repurchase intention among consumers, leveraging perceived product quality, perceived service quality, store atmosphere, perceived price, store location, and promotion. This study encompassed 120 respondents selected through non-probability sampling and purposive sampling techniques. The data collection instrument employed was a questionnaire, and data analysis was conducted using PLS-SEM. The findings revealed a significant and positive impact of perceived product quality, store atmosphere, and store location on brand image. Additionally, there was a significant and positive correlation between brand image and repurchase intention. However, perceived service quality, perceived price, and promotion exhibited no significant impact on brand image.